2009
DOI: 10.1097/ppo.0b013e3181a1437a
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radiation Therapy in Hodgkin’s Lymphoma

Abstract: Radiation therapy was the first modality that solely cured patients with Hodgkin's lymphoma (HL) as early as the 1940s. In the absence of other curative options, the radiation field in full dose was extended to encompass both involved and uninvolved sites including many normal organs. Decades later, it was evident that some of the HL survivors succumbed to radiation-related effects, mostly second solid tumors. The more recent reliance on modern chemotherapy in combination with radiation yielded further improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…[8-10, [15][16][17] Studies such as HD6 [12,18] may be unreliable to truly assess for OS as several deaths in the CMT arm were from unrelated causes. A more powerful meta-analysis of 1,245 patients demonstrated an OS benefit (HR=0.40) of CMT in early-stage HL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8-10, [15][16][17] Studies such as HD6 [12,18] may be unreliable to truly assess for OS as several deaths in the CMT arm were from unrelated causes. A more powerful meta-analysis of 1,245 patients demonstrated an OS benefit (HR=0.40) of CMT in early-stage HL.…”
Section: Discussionmentioning
confidence: 99%
“…[5,21] Fourth, this database does not include specific chemotherapy information regarding agents and number of cycles employed. To ensure that use of RT M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 15 represented consolidation treatment, we only included patients who underwent multi-agent chemotherapy regimens as standard practice at CoC-accredited centers.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of chemotherapy alone strategies believed an improved overall survival would be seen due to the reduction in late radiation related mortality. Furthermore, any increase in relapses seen in chemotherapy alone strategies would not affect survival because these patients could be salvaged with additional chemotherapy and stem-cell transplant (5). …”
Section: Introductionmentioning
confidence: 99%
“…The possibility cannot be excluded that such a highly significant difference in the incidence of complications (for such a small difference in the radiation dose) also may be caused in part by chance. However, recent retrospective studies have confirmed that, the lower the irradiation dose, the lower the incidence of secondary tumors and cardiac complications 23‐30. Because it was demonstrated recently that doses of 30 Gy were sufficient to sterilize lymphadenopathies that already had disappeared under chemotherapy,31‐33 it is plausible that, in patients with early HL who are in CR after a brief regimen of ABVD chemotherapy, irradiation doses of 25 Gy to 30 Gy limited to initially involved sites might be sufficient to maintain the high rate of FFTF observed in the current trial 32, 33…”
Section: Discussionmentioning
confidence: 57%